Web bloopers : 60 common web design mistakes and how to avoid them - Johnson, Jeff (Consultant) (Morgan Kaufmann series in interactive technologies., 2003)
Shows how to correct or avoid the blooper and gives an analysis of each design problem. This work discusses in detail 60 of the common web design mistakes, along with the solutions, challenges, and trade offs associated with them. It covers important subject areas such as: content, task-support, navigation, forms, searches, writing, and more.